Ventas por suscripción y la comercialización de un sistema de purificación de agua de uso doméstico - Chávez Camones, Pablo (2022)
The purpose of this research is to analyze the feasibility of the subscription sales model in the commercialization of a system of water purifiers for domestic use in the city of Guayaquil, in a post-pandemic context, with the purpose of offering families the possibility of access to the consumption of quality drinking water at reasonable prices. To determine the feasibility of the model, a mixed approach design with interpretive orientation was chosen, which combines quantitative elements derived from frequency analysis applied to the questionnaire with qualitative elements associated with discourse analysis applied to the interpretation of interviews conducted with experts in the matter. The information obtained was complemented with a thorough review of the literature related to marketing models and sales techniques to determine the administrative principles that govern them, their classification and structure. In the scenario described, the business should select as its target audience female subjects between 30 and 40 years old, with tertiary studies, professionals, with an already formed family, medium-high social status and a monthly income level greater than 1,606 dollars, interested in reducing domestic work after their working day outside the home and, with at least moderate sensitivity towards safeguarding both health and ecology. At the present time, the proposal is viable if the entrepreneur has sufficient capital to sustain it for the first three years, during which he will be forced to reinvest all the profits obtained in the business.